2020
DOI: 10.1186/s12985-020-01312-2
|View full text |Cite
|
Sign up to set email alerts
|

Isobavachalcone inhibits Pseudorabies virus by impairing virus-induced cell-to-cell fusion

Abstract: Pseudorabies virus (PRV) is an important pathogen that threatens the global swine industry. Currently, there is no effective drug that can clinically prevent or treat PRV infections. Isobavachalcone (IBC), a natural chalcone compound derived from Psoralea corylifolia, displays multiple biological activities, such as antibacterial, antifungal, and anticancer activities. Recently, it was found that IBC exhibited antiviral activity against an RNA virus, porcine reproductive and respiratory syndrome virus (PRRSV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Next, a cell-to-cell fusion assay was used to test whether these NAEK incorporation sites influenced gB mediated cell-to-cell fusion. As previously described, a transient transfection-based cell-to-cell fusion assay was performed by co-transfection of PTC gB, gD, gH, gL and EGFP plasmids [ 18 , 21 , 22 ]. The result indicated that some gB PTC sites such as 149Q, 169K, 185W, 206Q, 379K successfully induced syncytia formation in the presence of NAEK, and no syncytia was formed without NAEK ( Figure 2 F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, a cell-to-cell fusion assay was used to test whether these NAEK incorporation sites influenced gB mediated cell-to-cell fusion. As previously described, a transient transfection-based cell-to-cell fusion assay was performed by co-transfection of PTC gB, gD, gH, gL and EGFP plasmids [ 18 , 21 , 22 ]. The result indicated that some gB PTC sites such as 149Q, 169K, 185W, 206Q, 379K successfully induced syncytia formation in the presence of NAEK, and no syncytia was formed without NAEK ( Figure 2 F).…”
Section: Resultsmentioning
confidence: 99%
“…pCAGGS gB plasmid was previously described [ 18 ]. The amino acids at positions 149Q, 169K, 171K, 177K, 185W, 206Q, 217K, 221K, 267K, 285W, 319H, 331Q, 362W, 365W, 367W, 370K, 379K, and 413Q of gB protein were mutated to amber codon TAG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ISO is a chalcone that was first isolated from the multipurpose medical plant Psoralea corylifolia. Reportedly, ISO possesses a wide spectrum of antibacterial 38,39 antifungal 40 antiparasitic 41 , antiviral 42,43 , antitubercular 44 , antithrombotic 45,46 , antiinflammatory 47,48 , antioxidant 49 , antiobesity 50 , and phytoestrogene 51 activities. Hence, ISO has a very broad range of biological activities.…”
Section: Discussionmentioning
confidence: 99%
“…They were also found to act on important receptors such as CXCR4 chemokine receptors [41], US28 receptor of HCMV [27] and capsid pocket inside viral protein 1 (VP1) in rhinovirus [42]. Other important activities include targeting the kinase activity of epidermal growth factor receptor (EGFR) [27], inhibition of DNA hybridisation [30], mammalian target of rapamycin (mTOR) pathway [43], blocking virus-mediated cell fusion and inhibiting the late stages of viral replication [44]. In addition, chalcones were demonstrated by some studies to act as broad-spectrum covering agents on different viral infections and were shown to possess some preventive and prophylactic potential [45].…”
Section: Chalcones As Potential Candidates For Treating Viral Infectionsmentioning
confidence: 99%